Rethinking the categories of "Islam" and "Europe": theoretical and methodological issues - Γέρος, Παναγιώτης (The Greek Review of Social Research, 2016)
The article aims to explore the conceptualization of the relations between "Islam" and "Europe" through recent anthropological and social theory. I argue that the conventional and hegemonic perception of "Islam" in terms of "cultural otherness" is not only characterized by theoretical weakness but is also not capable of dealing, on a directly political level, with current tensions that often take the form of a religious/cultural clash. Instead of approaches that aim to manage the apparent "cultural difference" of Islam, it is suggested that we have to ethnographically and theoretically problematize the fundamental terms in which the difference between the categories of "Islam" and "Europe" is constructed.